Sexual Violence during War and Peace Gender, Power, and Post-Conflict Justice in Peru - Boesten, Jelke; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Using the Peruvian internal armed conflict as a case study, this book examines wartime rape and how it reproduces and reinforces existing hierarchies. Jelke Boesten argues that effective responses to sexual violence in wartime are conditional upon profound changes in legal frameworks and practices, institutions, and society at large.
Keywords: Science; Science; Science, general